The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3390/biomedicines11030968
|View full text |Cite
|
Sign up to set email alerts
|

Updates on Lymphovascular Invasion in Breast Cancer

Abstract: Traditionally, lymphovascular invasion (LVI) has represented one of the foremost pathological features of malignancy and has been associated with a worse prognosis in different cancers, including breast carcinoma. According to the most updated reporting protocols, the assessment of LVI is required in the pathology report of breast cancer surgical specimens. Importantly, strict histological criteria should be followed for LVI assessment, which nevertheless is encumbered by inconsistency in interpretation among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…Lymphovascular invasion is a known marker for worse survival outcomes in breast cancer, as well as a risk factor for local recurrence and distant metastases. Lymphovascular invasion is more commonly seen in larger tumors, Her2+, and TNBC subtypes [18]. In addition, we were able to associate node-positive disease with shorter tumor-to-nipple distance and smaller tumors in the Her2+ subset compared to others.…”
Section: Discussionmentioning
confidence: 55%
“…Lymphovascular invasion is a known marker for worse survival outcomes in breast cancer, as well as a risk factor for local recurrence and distant metastases. Lymphovascular invasion is more commonly seen in larger tumors, Her2+, and TNBC subtypes [18]. In addition, we were able to associate node-positive disease with shorter tumor-to-nipple distance and smaller tumors in the Her2+ subset compared to others.…”
Section: Discussionmentioning
confidence: 55%
“…However, this invasive approach often causes patient discomfort and its interpretation heavily relies on physician expertise. Therefore, it is imperative for clinicians to explore non-invasive and objective diagnostic methods in the detection of LVI [3].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that LVI is an important step in the invasion-metastasis cascade of BC, involves a complex molecular mechanism. In this process, invasive malignant cells invade the surrounding stroma, penetrate the vessel wall, and complete metastatic dissemination [3,4]. Therefore, the presence of LVI generally implies a high degree of malignancy in BC, which is closely related to reduced overall survival and poor prognosis [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Lymphovascular (LVI) and perineural invasion, defined as the presence of tumor emboli within an endothelium-lined space, has been associated with worst outcomes and increased probability of distant metastases in breast cancer [30]. Tumor budding has been established as a predictor of lymphovascular invasion for colorectal cancer [31].…”
Section: Discussionmentioning
confidence: 99%